Solid waste management in developing urban areas : case study of Lwandle Township - Puling, Leloko; Van der Merwe, J. H. (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MSc (Geography and Environmental Studies))--University of Stellenbosch, 2004.